Between Truth and Relativism: the Choice of Psychoanalysis - Brusa, Luisella (Filozofski vestnik, 2013)
My aim in this paper is to draw attention to the position of psychoanalysis regarding the opposition between the quest for truth and relativism. It is a conventional opposition of contemporary thought. On one hand, the quest for truth, and on the other, relativism, as the fundament of our intellectual and political life. I do this by means of Lacanian teachings. My objective is to take on the theoretical tools of psychoanalysis and the consequences of clinical facts, in order to enable a critical reflection on this topic. Before proceeding to the precise argument, I briefly introduce the historical ground correlated to modern subjectivity, characterized by the vanishing of the guarantee of both truth and knowledge. Then I then go into the topic by means of a survey of Lacan’s reading of the path of modern logic. Lacan interprets the whole history of logic as a bungled action, “every bungled action is a successful discourse.” In fact, it points to the cardinal place of lack, which is the topic of psychoanalysis. It opens towards a deeper understanding of the role of the signifier of signification – the Bedeutung des Phallus. Lacan’s interpretation of the whole history of logic transforms the achievements of modern logical thought into the writings of a point de capiton for collective rationality. The key here is to focus on the capital role of what I call in conclusion “an inaccessible point” for both individual and collective life. This is the issue I address in the last point. The article is divided into five points: 1. the relativistic drift; 2. the guarantee of knowledge; 3. the guarantee of truth; 4. logic and point de capiton; and 5. the signification (Bedeutung) of the Phallus.